The Effects of Cold Application to the Perineum on Pain Relief After Vaginal Birth - Derya K. Senol, Ph.D., RN; Ergul Aslan, RN (Asian Nursing Research, 2017)
Purpose: Perineal pain developing during the postpartum period affects women's relationships with their families and infants. The aim of this study was to determine the efficacy of cold gel pad application for relieving perineal pain and possibly increasing mothers' comfort after vaginal delivery. Methods: This experimental randomized controlled study was conducted in the postpartum department of obstetrics and gynecology hospital. A total of 200 mothers were included in the study. Cold gel pads were applied to the perineum of mothers in the experimental group for 20 minutes in the postpartum first 2 hours and 4 hours after the first application. All the data were collected by using an information form, the visual analog scale, and the postpartum comfort questionnaire. Results: In the experimental group, the first visual analog scale score was 6.73 ± 1.68; after cold gel pad application, the pain levels decreased to 2.59 ± 1.20 in both primiparous and multiparous mothers. In addition, the postpartum comfort questionnaire score increased from 2.58 ± 0.14 to 2.69 ± 0.14 in the second assessment after the cold gel pad application and the difference was statistically significant (p < .001). Conclusion: The application of the cold gel pad to the perineum relieved perineal pain and increased postpartum comfort in all the women. The pain felt by the women during the recovery and the daily activities decreased. Postpartum perineal pain adversely affected daily activities such as lying down, sitting, and walking; infant care, breastfeeding, and urination; and comfort levels of the postpartum women. Keywords: pain, perineum, postpartum period